A diaphragm for producing hydrogen by electrolysis of water with a burr structure and a preparation method thereof

By adopting a composite porous layer with a burr structure and a support wire mesh, the existing diaphragm has poor toughness, high powder drop rate, high surface resistance and high energy consumption, the effects of low powder drop, low surface resistance and low energy loss are achieved, and the service life of the diaphragm and electrolytic cell components are extended.

CN119243248BActive Publication Date: 2025-04-04JIANGSU NEW HORIZON ADVANCED FUNCTIONAL FIBER INNOVATION CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411357710.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-04
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing electrolytic water hydrogen-making diaphragm has problems such as poor toughness, easy powder loss, high surface resistance, high energy consumption during electrolysis, and the seals in various parts of the supporting electrolytic tank are prone to aging at high temperature.

Method used

The electrolytic hydro-making hydrogen separator consisting of a composite porous layer with a burr structure and a supporting wire mesh is used. The composite porous layer contains alkali-resistant polymers, hydrophilic modified inorganic substances and hydrophilic modification auxiliary agents. The burr-like pore structure with large pore diameter vertical through holes and mesh composite small pores is prepared.

Benefits of technology

The diaphragm is achieved with low powder loss rate, low surface resistance and low energy loss, which improves the toughness and voltage resistance of the diaphragm, and extends the service life of the diaphragm and electrolytic cell components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243248B_ABST
    Figure CN119243248B_ABST
Patent Text Reader

Abstract

The present invention relates to a water electrolysis hydrogen production diaphragm with a burr structure and a preparation method thereof, belonging to the technical field of hydrogen production diaphragms, and solving at least one of the problems in the prior art, such as high surface resistance of hydrogen production diaphragms, high electrolysis voltage, and large power loss during hydrogen production. The present invention provides a water electrolysis hydrogen production diaphragm with a burr structure, the diaphragm is composed of a supporting wire mesh and a composite porous layer with a burr structure, the supporting wire mesh is located in the middle of the composite porous layer; the composite porous layer has vertical through holes with large apertures and mesh composite pores, and the vertical through holes and mesh composite pores are all burr-shaped holes. The diaphragm is suitable for hydrogen production by alkaline water electrolysis at room temperature, has high ion permeability, low surface resistance, good pressure resistance and air tightness, and a standard surface resistance of ≤0.1Ω / cm at room temperature. 2 , at an electrolysis temperature of 90°C and a current density of 5000A / m 2 Under the test conditions, the cell voltage was ≤1.05V, which significantly reduced the energy loss during the electrolysis process. The diaphragm also verified the feasibility of hydrogen production by room temperature electrolysis and can effectively alleviate the thermal aging of electrolyzer components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production diaphragms, and in particular to a water electrolysis hydrogen production diaphragm with a burr structure and a preparation method thereof. Background Art

[0002] Alkaline water electrolysis is one of the main ways to produce green hydrogen (green hydrogen). It uses an alkaline electrolyzer to decompose water molecules into hydrogen and oxygen. This technology has significant environmental advantages because it can rely entirely on renewable energy sources such as solar and wind energy to achieve clean production of hydrogen. The alkaline electrolyzer is the core equipment in this process. It consists of electrode plates, diaphragms and alkaline electrolytes. The electrode plates are usually made of nickel or nickel alloys and are responsible for transmitting current during the electrolysis process. The diaphragm is a special material that plays a vital role in the electrolyzer: on the one hand, it isolates hydrogen and oxygen to prevent safety risks that may be caused by the mixing of the two gases; on the other hand, it allows water molecules to pass through while maintaining ion conduction, thereby maintaining the electrolysis reaction. The performance of the diaphragm directly affects the purity of hydrogen and the energy efficiency of the electrolysis process.

[0003] High-quality diaphragms can improve the purity of hydrogen output, reduce energy consumption, and lower production costs. With the development of technology, new diaphragm materials such as composite membranes and non-asbestos membranes are being developed and applied to improve the performance and safety of electrolyzers. Alkaline water electrolysis hydrogen production technology plays an important role in the future clean energy field. At present, the operating temperature of alkaline electrolysis hydrogen production cells is generally between 85 and 95 °C. This is because OH in the water electrolysis process - Resistance is generated when passing through the diaphragm layer. When the temperature is increased, the mobility of ions is enhanced and the resistance is reduced. However, the high temperature during alkaline electrolysis will produce a large amount of energy loss, and the aging speed of the diaphragm will be accelerated at high temperature, reducing the service life of the diaphragm, and accelerating the aging of seals in various parts of the electrolytic cell.

[0004] In summary, the existing water electrolysis hydrogen production diaphragms have problems such as poor toughness, easy powder loss, high surface resistance, high energy consumption during electrolysis, and aging of seals in various parts of the matching electrolytic cell. Summary of the invention

[0005] In view of the above analysis, an embodiment of the present invention aims to provide a water electrolysis hydrogen production diaphragm with a burr structure and a preparation method thereof, so as to solve at least one of the problems of the existing water electrolysis hydrogen production diaphragm, such as poor toughness, easy powder loss, high surface resistance, high energy consumption during electrolysis, and easy high temperature aging of seals in various parts of the matching electrolytic cell.

[0006] The present invention provides a water electrolysis hydrogen production diaphragm with a burr structure, wherein the diaphragm is composed of a supporting wire mesh and a composite porous layer with a burr structure, wherein the supporting wire mesh is located in the middle of the composite porous layer;

[0007] The composite porous layer has vertical through holes with large apertures and mesh composite small holes, and the vertical through holes and mesh composite small holes are all burr-shaped holes;

[0008] The diameter of the large-aperture vertical through hole is 15 to 45 microns, and the diameter of the mesh composite small hole is 2 to 8 microns;

[0009] The composite porous layer contains an alkali-resistant polymer, a hydrophilic modified inorganic substance and a hydrophilic modified auxiliary agent.

[0010] Specifically, the material of the support mesh is polyphenylene sulfide (PPS) or polyetheretherketone (PEEk); the support mesh is woven from monofilaments, the weaving density is 20-100 meshes, and the diameter of the monofilaments is 30-150 microns.

[0011] Specifically, the burr structure has a hydrophilic surface and a capillary effect.

[0012] Specifically, the thickness of the diaphragm is 300-500 μm; the standard surface resistance at room temperature is ≤0.1 Ω / cm 2 , at an electrolysis temperature of 90°C and a current density of 5000A / m 2 Under the test conditions, the cell voltage is ≤1.05V.

[0013] The present invention also discloses a method for preparing the diaphragm, firstly, a casting liquid is prepared according to a preset formula, wherein the casting liquid contains a pore-forming agent, a pore-forming auxiliary agent, an organic solvent, an alkali-resistant polymer, a hydrophilic modification auxiliary agent and a hydrophilic modified inorganic substance; then, a supporting wire mesh is prepared, and the casting liquid is scraped onto the surface of the supporting wire mesh to obtain a semi-finished diaphragm; finally, the diaphragm is cured in a coagulation bath and post-treated to obtain a finished diaphragm.

[0014] The specific steps include:

[0015] S1: dissolving the pore-forming agent and the pore-forming auxiliary agent in an organic solvent, adding an alkali-resistant polymer after dissolution and ensuring complete dissolution, to obtain a mixed solution I;

[0016] S2: adding a hydrophilic modification auxiliary agent to the mixed solution I and mixing evenly, slowly adding the hydrophilic modification inorganic powder under stirring conditions, stirring until no obvious particles are present, and then cooling to obtain a casting solution;

[0017] S3: prepare a supporting screen, set the height of the scraper to a preset thickness, use the casting liquid obtained in S2 to scrape the film, and let it stand for a period of time after the scraping is completed to obtain a semi-finished diaphragm;

[0018] S4: Immerse the semi-finished diaphragm in a coagulation bath for solidification, and after the diaphragm is completely solidified, wash it with deionized water to obtain a finished diaphragm.

[0019] Furthermore, the pore-forming agent is compounded by polyvinyl pyrrolidone (PVP) of different molecular weights;

[0020] The compounding relationship is: the molecular weight of the high molecular weight PVP is 80w-150w, the molecular weight of the low molecular weight PVP is 28000-54000, the mass ratio of the high molecular weight PVP to the low molecular weight PVP is 5-6:5-6; the total mass of the pore-forming agent is 50-75% of the mass of the alkali-resistant polymer.

[0021] Specifically, the pore-forming auxiliary agent is gum arabic, and the mass of the pore-forming auxiliary agent is 10-15% of the mass of the alkali-resistant polymer.

[0022] Specifically, the hydrophilic modified inorganic substance is one or more of nano zirconium oxide, nano titanium oxide and nano cerium oxide; the added amount is 80-120% of the mass of the alkali-resistant polymer.

[0023] Specifically, the hydrophilic modification auxiliary agent is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, fatty acid methyl ester ethoxylate sodium sulfonate, and alkylphenol polyoxyethylene ether; the mass of the hydrophilic modification auxiliary agent is 15-28% of the mass of the alkali-resistant polymer.

[0024] Specifically, the solution used in the coagulation bath in step S4 is one or more of deionized water, NMP, DMAC, ethanol, and methanol, and the temperature is 10-45°C.

[0025] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0026] 1. The water electrolysis hydrogen production diaphragm with a burr structure provided by the present invention has the advantages of low powder loss rate, low surface resistance and small energy loss during water electrolysis.

[0027] The hydrogen-producing diaphragm provided by the present invention adopts the main structure of "composite porous layer + supporting wire mesh". The supporting wire mesh serves as the "flexible skeleton" of the diaphragm and the load matrix of the composite porous layer. On the one hand, it provides tensile strength for the diaphragm. On the other hand, it supports the porous layer internally and thus enhances its resistance to air pressure and hydraulic pressure, thereby ensuring the strength and toughness of the finished diaphragm, making the diaphragm more tough and less prone to breakage.

[0028] The composite porous layer of the hydrogen production membrane has vertical through holes with large apertures and mesh composite small holes, and the vertical through holes and mesh composite small holes are burr-like holes; the composite mesh porous structure helps to improve the water permeability and ion permeability of the membrane.

[0029] Specifically, the present invention adopts an innovative formula of "compounded pore-forming agent + pore-forming auxiliary agent (gum arabic)" in the preparation process of the diaphragm, and prepares a composite porous layer having both vertical through holes (corresponding to low molecular weight pore-forming agent) and network composite small holes (corresponding to high molecular weight pore-forming agent) based on the characteristics of different chain lengths, spatial distribution and volumes of pore-forming agents of different molecular weights; low molecular weight pore-forming agents, such as PVP, exchange quickly during the phase inversion process and can form vertical through holes, and high molecular weight pore-forming agents, such as PVP, exchange slowly during the phase inversion process and mainly form network small holes; the diameter of the large-aperture vertical through holes in the composite porous layer prepared by the above-mentioned compound pore-forming agent is 15 to 45 microns, and the diameter of the network composite small holes is 2 to 8 microns, which has good ion permeability and hydrophilicity;

[0030] Due to the synergistic effect of the pore-forming auxiliary agent and the pore-forming agent, the pore-forming auxiliary agent is adsorbed on the surface of the pore-forming agent during the scraping step, thereby turning the "smooth surface" of the pore-forming agent into an "irregular surface with burrs". After the pore-forming agent and the pore-forming auxiliary agent are removed in the coagulation bath or washing stage (i.e., the phase inversion process), holes with burr-like inner walls (including through holes and composite small holes) are obtained. The special burr structure enhances the capillary effect, enhances the alkali absorption rate and OH absorption of the diaphragm - The diffusion efficiency (i.e., ion permeability) of the diaphragm is improved, while the pressure resistance and air tightness of the diaphragm are guaranteed. Pressure resistance is a safety requirement for the diaphragm. When water electrolysis is used to produce hydrogen, the diaphragm needs to withstand a certain water pressure. If the pressure resistance is poor, the diaphragm may be damaged, affecting safety. Air tightness determines the purity of hydrogen produced by water electrolysis. The higher the air tightness, the smaller the probability of hydrogen and oxygen generated by the anode and cathode interacting with each other, and the higher the purity. It is worth noting that the burr structure has a strong capillary effect and a hydrophilic surface, which helps to improve the hydrophilicity of the diaphragm.

[0031] The hydrophilic modified inorganic substance and the hydrophilic modified auxiliary agent are used in combination in the present invention, which reduces the amount of hydrophilic modified inorganic substance (such as zirconium oxide) added compared with the prior art, reduces the proportion of inorganic particles in the diaphragm to a certain extent, and improves the phenomenon of diaphragm powder falling.

[0032] After testing, the standard surface resistance of the diaphragm provided by the present invention is ≤0.1Ω / cm 2 , at an electrolysis temperature of 90°C and a current density of 5000A / m 2 Under the test conditions, the chamber voltage is ≤1.05V, which can significantly reduce the energy loss in the process of water electrolysis, and can appropriately reduce the process temperature of water electrolysis to produce hydrogen, and even directly use room temperature alkaline electrolyzer and room temperature electrolysis process, which indirectly protects the electrolyzer components and slows down the thermal aging of seals.

[0033] 2. The hydrogen production membrane and the supporting preparation method provided by the present invention have simple preparation process, relatively easy-to-obtain raw materials, low operation difficulty, mild process conditions, good application prospects, and are suitable for large-scale production and large-scale promotion.

[0034] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0036] Figure 1 A schematic diagram of the structure of a water electrolysis hydrogen production diaphragm with a burr structure;

[0037] Figure 2 This is an electron microscope photo of the microstructure of the diaphragm in Example 1 (100 μm scale);

[0038] Figure 3 This is an electron microscope photograph of the burr structure of the diaphragm in Example 1 (10 μm scale). DETAILED DESCRIPTION

[0039] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0040] After extensive literature research, the inventors found that the current composite membranes used for alkaline hydrolysis to produce hydrogen still have the following problems and shortcomings. Through a large amount of experimental exploration and theoretical analysis, the inventors accurately located the causes and mechanisms of the defects.

[0041] Defect location:

[0042] (1) The current PPS fabric diaphragms and composite diaphragms have problems such as low ion permeability, insufficient hydrophilicity and alkalinity.

[0043] (2) Due to the limited ion permeability and alkalinity of the commercially available alkaline water electrolysis hydrogen production diaphragm, it must be operated at high temperature (85-90°C) to increase the ion permeability of hydroxide to reduce DC power consumption. However, high temperature requires the addition of an additional heating device to the electrolyzer, which increases energy loss. High temperature also accelerates the aging of parts such as sealing gaskets and diaphragms, increasing the maintenance and use cost of the electrolyzer.

[0044] (3) The proportion of inorganic matter (mainly hydrophilic oxides represented by zirconium oxide) in the current composite diaphragm is too high (more than 65%), the diaphragm is brittle and tough, and the diaphragm is easily damaged during installation and transportation. The operating temperature of the current alkaline electrolysis hydrogen production cell is generally 85-95°C. This is because OH - Resistance is generated when passing through the diaphragm layer. When the temperature is increased, the mobility of ions is enhanced and the resistance is reduced. However, the high temperature during alkaline electrolysis will produce a large amount of energy loss, and the aging speed of the diaphragm will be accelerated at high temperature, reducing the service life of the diaphragm, and accelerating the aging of seals in various parts of the electrolytic cell.

[0045] Cause Analysis:

[0046] Research has found that the stronger the hydrophilicity of the diaphragm and the better the water permeability, the lower the surface resistance. The surface resistance of the diaphragm has a marginal effect as the temperature decreases. When the resistance is small enough at room temperature, the ion permeability is gradually affected by the temperature.

[0047] In response to the above problems, the present invention designs a water electrolysis hydrogen production diaphragm with a burr structure. By preparing a composite diaphragm with a special burr composite pore microstructure, a lower current loss can be achieved at room temperature without the need for additional heating equipment.

[0048] The present invention provides a water electrolysis hydrogen production diaphragm with a burr structure, wherein the diaphragm is composed of a supporting wire mesh and a composite porous layer with a burr structure, wherein the supporting wire mesh is located in the middle of the composite porous layer;

[0049] Specifically, the support wire mesh serves as the "flexible skeleton" of the diaphragm and the load matrix of the composite porous layer. On the one hand, it provides tensile strength for the diaphragm, and on the other hand, it supports the porous layer internally to enhance its air pressure and hydraulic pressure resistance, thereby ensuring the strength and toughness of the finished diaphragm, making the diaphragm more tough and less prone to breakage.

[0050] The composite porous layer has large-diameter vertical through holes and mesh-like composite small holes, and the vertical through holes and mesh-like composite small holes are all burr-like holes; the composite structure of large-diameter vertical through holes and mesh-like composite small holes, combined with the burr structure of the inner wall of the hole (such as Figure 3 As shown in the figure), the capillary effect of the composite porous layer is enhanced, thereby enhancing the alkali absorption rate and OH - The diffusion efficiency (i.e. ion permeability) is improved, while ensuring the pressure resistance and air tightness of the diaphragm;

[0051] The diameter of the large-aperture vertical through hole is 15 to 45 microns, and the diameter of the mesh composite small hole is 2 to 8 microns. The composite porous layer structure of the above size has good ion permeability and hydrophilicity;

[0052] The composite porous layer contains an alkali-resistant polymer, a hydrophilic modified inorganic substance and a hydrophilic modified auxiliary agent.

[0053] Specifically, the alkali-resistant polymer serves as the matrix of the porous layer. The alkali-resistant polymer is polysulfone (PSF) or other alkali-resistant polymers soluble in polar solvents or modified forms of polysulfone (such as sulfonated polysulfone, etc.), preferably polysulfone. The mass proportion of the alkali-resistant polymer in the dry film is 35-55%.

[0054] Specifically, the role of the hydrophilic modified inorganic substance is to improve the hydrophilic wettability of the diaphragm, and the hydrophilic modified inorganic substance is one or more of materials such as nano zirconium oxide, nano titanium oxide, and nano cerium oxide; the oxygen ions in the metal oxide can form hydrogen bonds with water molecules in the electrolyte, thereby improving the hydrophilicity of the diaphragm and improving the compatibility with the electrolyte. The above-mentioned nano metal oxides have strong surface activity and can work together with the alkali-resistant polymer and the hydrophilic modified auxiliary agent to improve the water permeability of the diaphragm;

[0055] In general, smaller nano-inorganic particles have a larger specific surface area and better hydrophilic modification performance. However, when the particle size is too small, the inorganic particles will agglomerate and cannot be evenly dispersed in the casting liquid (subsequently forming a composite porous layer). Therefore, the particle size of the nano-inorganic particles should be moderate. After experimental screening, the particle size of the nano-inorganic particles should be controlled at 5-100nm, preferably 15-25nm, such as 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25nm; if the amount of hydrophilic modified inorganic substance added is too low, the hydrophilic wetting performance of the diaphragm will be damaged; if the amount added is too high, the toughness of the diaphragm will decrease and the risk of powder falling will be increased; the amount of hydrophilic modified inorganic substance accounts for 45-60% of the mass of the final dry film, preferably 50-55%, such as 50, 51, 52, 53, 54, 55%.

[0056] Specifically, the role of the hydrophilic modification auxiliary agent is to assist in improving the hydrophilic wetting performance of the diaphragm. The functional groups such as ether bonds in the modified auxiliary agent can form hydrogen bonds to enhance the hydrophilicity, so that the composite porous layer has good hydrophilicity and wetting performance; in fact, the presence of the hydrophilic modification auxiliary agent can reduce the amount of hydrophilic modified inorganic substances added while ensuring good hydrophilic wettability of the diaphragm, which helps to improve the toughness and powder loss rate of the diaphragm. The hydrophilic modification auxiliary agent is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, sodium fatty acid methyl ester ethoxylate sulfonate, and alkylphenol polyoxyethylene ether. If the content is too low, the hydrophilic wetting performance of the diaphragm is insufficient; if the content is too high, the alkali-resistant polymer cannot be completely fixed and will precipitate from the alkali-resistant polymer. The mass proportion of the hydrophilic auxiliary modifier in the dry film is 5-10%, for example, 5, 6, 7, 8, 9, 10%.

[0057] Specifically, the material of the support mesh is polyphenylene sulfide (PPS) or polyetheretherketone (PEEk); the support mesh is woven from monofilaments, the weaving density is 20-100 meshes, such as 20, 30, 50, 70, 100 meshes, and the diameter of the monofilaments is 30-150 microns, such as 30, 40, 50, 60, 70, 80, 90, 100, 120, 150 microns. Polyphenylene sulfide (PPS) or polyetheretherketone (PEEk) are the two most commonly used alkali-resistant engineering plastics with super mechanical properties, among which PPS is cheaper and more cost-effective, so it is preferred.

[0058] Specifically, the single wire diameter of the supporting wire mesh is lower and the weaving density is higher. The weaving density and diameter of the wire mesh should match the thickness of the diaphragm. When the weaving density and the single wire diameter meet the above requirements, the comprehensive performance of the supporting wire mesh is better.

[0059] Specifically, the burr structure surface is hydrophilic and has a capillary effect. The hydrophilicity of the burr structure surface can further improve the water permeability of the diaphragm, thereby reducing the surface resistance of the diaphragm. In addition, the capillary effect helps to improve the water permeability and ion permeability of the diaphragm, and helps to reduce the energy loss in the process of hydrogen production by electrolysis of water.

[0060] Specifically, the thickness of the diaphragm is 300-500 μm; the standard surface resistance at room temperature is ≤0.1 Ω / cm 2 , at an electrolysis temperature of 90°C and a current density of 5000A / m 2 Under the test conditions, the cell voltage is ≤1.05V.

[0061] It is worth noting that, under room temperature conditions, the cell voltage of the diaphragm can reach the level of existing diaphragms under 90°C conditions, which means that the room temperature alkaline electrolysis process can replace the traditional high temperature / heating alkaline electrolysis process, thereby reducing energy consumption and slowing down thermal aging of related components of the electrolytic cell.

[0062] The present invention also discloses a method for preparing the diaphragm, which specifically comprises the following steps:

[0063] S1: dissolving the pore-forming agent and the pore-forming auxiliary agent in an organic solvent, adding an alkali-resistant polymer after dissolution and ensuring complete dissolution, to obtain a mixed solution I;

[0064] S2: adding a hydrophilic modification auxiliary agent to the mixed solution I and mixing evenly, slowly adding the hydrophilic modification inorganic powder under stirring conditions, stirring until no obvious particles are present, and then cooling to obtain a casting solution;

[0065] S3: prepare a supporting screen, set the height of the scraper to a preset thickness, use the casting liquid obtained in S2 to scrape the film, and let it stand for a period of time after the scraping is completed to obtain a semi-finished diaphragm;

[0066] S4: Immerse the semi-finished diaphragm in a coagulation bath for solidification, and after the diaphragm is completely solidified, wash it with deionized water to obtain a finished diaphragm.

[0067] In the process of preparing the diaphragm, firstly, the organic solvent, hydrophilic modified inorganic substance, alkali-resistant polymer, hydrophilic modified auxiliary agent, pore-forming agent, and pore-forming auxiliary agent are prepared into a casting liquid according to a preset ratio, and the above components are evenly distributed in the casting liquid; wherein the pore-forming auxiliary agent is combined with the surface of the pore-forming agent in the form of adsorption, etc., and together realizes "placeholder" pore making. After the above casting liquid is used for scraping, in the coagulation bath stage, the casting liquid gradually solidifies into a composite porous layer. Since the pore-forming agent and pore-forming auxiliary agent therein are removed in the coagulation bath (ie, the phase inversion stage) and the washing stage, the preparation of large-diameter vertical through holes and mesh composite small holes is realized, and the pore-forming auxiliary agent ensures that the inner wall of the hole has a burr structure; the organic solvent will also be removed in the coagulation bath stage. Alkali-resistant polymers, hydrophilic modified inorganic substances and hydrophilic modified auxiliary agents will not be lost or the loss amount is very small, thereby forming a composite porous layer.

[0068] It is worth noting that the composite network porous structure combining large and small pores is mainly a technical effect brought about by the compounded pore-forming agent, and the specific parameters of the subsequent coagulation bath (phase inversion) and washing stage play an auxiliary role in the formation of the composite network porous structure.

[0069] It is worth noting that, although the various components are added separately in the specific preparation process, in order to facilitate the implementation of the technical personnel, the overall composition of the casting solution is given so that the raw materials can be prepared in advance during the specific implementation process.

[0070] Specifically, the specific composition of the casting solution in step S2 is calculated by mass as follows: 360 to 520 parts of organic solvent, 80 to 120 parts of hydrophilic modified inorganic substance, 100 parts of alkali-resistant polymer, 15 to 28 parts (preferably 18 to 25 parts) of hydrophilic modified auxiliary agent, 50 to 75 parts of pore-forming agent, and 10 to 15 parts of pore-forming auxiliary agent.

[0071] Specifically, the pore-forming agent (PVP) is given priority in the preparation process because PVP, in addition to its pore-forming function, is also an excellent dispersant, which helps to disperse the subsequent components; the hydrophilic modified auxiliary agent and hydrophilic modified inorganic substance are placed last in order to reduce the impact on the dispersion or dissolution of other components.

[0072] Specifically, the organic solvent is one or more of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC) or other polar solvents that can dissolve the above-mentioned alkali-resistant polymer, organic hydrophilic modifier and pore-forming agent, preferably NMP, which has the best dissolution effect. The organic solvent plays the role of dissolving components such as polymers and pore-forming agents. If the solvent is too little, the polymer becomes more difficult to dissolve, the viscosity of the casting liquid is too high and the fluidity becomes poor, which is not suitable for scraping the film, the washing difficulty of the finished film increases, and the pore structure is reduced, affecting the ion permeability; too much solvent causes material waste, the fluidity of the casting liquid is too high, the thickness of the film layer cannot be guaranteed, and the morphology of the porous layer cannot be maintained after phase inversion. Preferably, the amount of the organic solvent added is 360-520% of the alkali-resistant polymer, such as 360%, 380%, 400%, 420%, 450%, 480%, 500%, 520%.

[0073] Specifically, the alkali-resistant polymer serves as the matrix of the porous layer, and its content is exactly opposite to that of the solvent. If the content is too high, it becomes difficult to dissolve the polymer, the viscosity of the casting liquid is too high, and the fluidity becomes poor, making it unsuitable for scraping the film. The washing of the finished film becomes more difficult, and the pore structure is reduced, affecting the ion permeability. If the content is too little, the fluidity is too high, the fluidity of the casting liquid is too high, and the thickness of the membrane layer cannot be guaranteed, and the morphology of the porous layer cannot be maintained after phase inversion.

[0074] Optionally, the alkali-resistant polymer is polysulfone (PSF) or other alkali-resistant polymers soluble in polar solvents or modified polysulfones (such as sulfonated polysulfone, etc.), preferably polysulfone. Polysulfone has significant advantages such as high alkali resistance, good mechanical properties and dimensional stability at high temperatures as a raw material for alkaline water electrolysis hydrogen production diaphragm. And compared with other high-performance materials, polysulfone provides a good balance between cost and performance, making it more economical in large-scale applications.

[0075] Specifically, the hydrophilic modified inorganic substance is one or more of nano zirconium oxide, nano titanium oxide and nano cerium oxide. Nano zirconium oxide is the best in terms of hydrophilic modification effect and cost. Preferably, the addition amount of the hydrophilic modified inorganic substance is 80-120% of the alkali-resistant polymer, such as 80%, 85%, 90%, 95%, 100%, 105%, 110%, 115%, 120%.

[0076] Specifically, the hydrophilic modification auxiliary agent is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, fatty acid methyl ester ethoxylate sodium sulfonate, and alkylphenol polyoxyethylene ether; the mass of the hydrophilic modification auxiliary agent is 15-28% of the mass of the alkali-resistant polymer, preferably 18-25%, such as 18%, 19%, 20%, 21%, 22%, 23%, 24%, and 25%.

[0077] Furthermore, the pore-forming agent is compounded by polyvinyl pyrrolidone (PVP) of different molecular weights;

[0078] The compounding relationship is: the molecular weight of high molecular weight PVP is 80w-150w, the molecular weight of low molecular weight PVP is 28000-54000, and the mass ratio of high molecular weight PVP to low molecular weight PVP is 5-6:5-6;

[0079] The compound relationship between high molecular weight PVP and low molecular weight PVP mainly affects the formation of the composite structure of large through holes and mesh holes. Low molecular weight PVP exchanges quickly during the phase transformation process and can form vertical through holes. High molecular weight PVP exchanges slowly during the phase transformation process and mainly forms mesh holes. If the proportion of low molecular weight PVP is too large, the large pore structure cannot withstand the phase transformation process and collapses, and the pressure resistance of the diaphragm deteriorates. If the proportion of high molecular weight PVP is too large, through holes cannot be formed, ion permeability decreases sharply, the phase transformation time is too long, and the diaphragm is not easy to wash. By adjusting the ratio of the two, a diaphragm structure with both high ion exchange rate and pressure resistance can be adjusted.

[0080] If the content of the pore-forming agent is too low, a pore structure of sufficient quantity and size cannot be prepared. If the content is too high, the pores will be too large or the structural strength will be insufficient. The total mass of the pore-forming agent is 50-75% of the mass of the alkali-resistant polymer, such as 50%, 55%, 60%, 65%, 70%, and 75%.

[0081] Specifically, the pore-forming auxiliary agent is gum arabic, and the mass of the pore-forming auxiliary agent is 10-15% of the mass of the alkali-resistant polymer, such as 10%, 11%, 12%, 13%, 14%, 15%. The function of the pore-forming auxiliary agent is to assist in forming a burr-like papillary pore structure, and its content ratio is obtained after a large number of experimental verifications and adjustments. If the content is too small, the corresponding burr-like papillary structure cannot be formed (such as Figure 3 If the content is too high, the inherent composite structure of large through holes and mesh-like small holes will be destroyed.

[0082] It is worth emphasizing that during the film laying process (generally using a film scraper), care should be taken to ensure that the supporting screen is completely immersed in the film casting liquid, but it does not need to be in the middle; in particular, the screen peeling and exposure after film laying should be avoided, otherwise it will affect the overall performance of the diaphragm. The film laying thickness mainly includes two requirements. On the one hand, the supporting screen must be completely covered, and on the other hand, it is necessary to provide the diaphragm with sufficient air tightness and pressure resistance. Measured by the bubble point, the thicker the film, the higher the bubble point, the better the air tightness and pressure resistance, but the thicker the thickness, the worse the ion permeability, and the greater the power loss during hydrogen electrolysis. Combining the above two points and the current process level, the thickness of the diaphragm should be between 300 and 500 microns, such as 300 microns, 310 microns, 320 microns, 350 microns, 380 microns, 400 microns, 420 microns, 450 microns, 480 microns, and 500 microns.

[0083] Specifically, the solution used in the coagulation bath in step S4 is one or more of deionized water, NMP, DMAC, ethanol, and methanol, and the temperature is 10-45° C. The solution and temperature selection mainly affect the pore morphology and phase conversion efficiency, and are mutually matched and corresponding to the front-end casting solution formula. It has been verified by experiments that the above conditions are more favorable for the formation of pores.

[0084] Furthermore, there are no special requirements for the washing process. The main purpose is to clean the organic solvents, pore-forming agents, pore-forming auxiliary agents and unfixed hydrophilic modified inorganic substances and hydrophilic modified auxiliary agents in the diaphragm. The specific requirements are to clean the diaphragm and the temperature should not be too high to cause excessive dimensional shrinkage. Taking the above into consideration, the washing temperature is between 60 and 90°C, preferably 80°C.

[0085] Example 1

[0086] Preparation of 500 μm (preset thickness) diaphragm:

[0087] Weigh 41.25g PVP k30, 41.25g PVP k88-96, and 14g gum arabic and dissolve them in 550g NMP. After thorough dissolution, add 125g polysulfone and ensure complete dissolution. Add 16g fatty alcohol polyoxyethylene ether, 3g oleic acid polyoxyethylene ether, and 3g fatty acid methyl ester ethoxylate sodium sulfonate and mix well. After the above materials are mixed well to obtain a transparent solution, slowly add 125g 20-micron zirconium oxide powder while stirring at a speed of 1200rpm, stir until there are no obvious particles, and then cool to obtain a casting solution. Select a 25-mesh, 130-micron diameter polyphenylene sulfide monofilament screen, adjust the scraper height limit to 520 microns, use the configured casting liquid to scrape the film, let it stand for about 15 seconds after scraping, and immerse the film directly in a coagulation bath for curing. The coagulation bath is pure deionized water at a temperature of 30°C. After 5 minutes of complete curing, transfer the diaphragm to 80°C deionized water and thoroughly wash it to obtain the finished product.

[0088] Example 2

[0089] Preparation of 300 micron (preset thickness) diaphragm: weigh 40g PVP k30, 40g PVP k88-96, and 16g gum arabic and dissolve them in 500g NMP. After thorough dissolution, add 140g polysulfone and ensure complete dissolution. Add 18g fatty alcohol polyoxyethylene ether, 4g oleic acid polyoxyethylene ether, and 4g fatty acid methyl ester ethoxylate sodium sulfonate and mix evenly. After the above materials are mixed evenly to obtain a transparent solution, slowly add 140g 20-micron zirconium oxide powder while stirring at a speed of 1200rpm, stir until there are no obvious particles, and then cool to obtain a casting solution. Select a 200-mesh, 70-micron diameter polyphenylene sulfide monofilament screen, adjust the scraper height limit to 320 microns, use the configured casting liquid to scrape the film, let it stand for about 15 seconds after scraping, and immerse the film directly in a coagulation bath for curing. The coagulation bath is pure deionized water at a temperature of 30°C. After 5 minutes of complete curing, transfer the diaphragm to 80°C deionized water and thoroughly wash it to obtain the finished product.

[0090] To test the performance of the diaphragm, we used the SJ / T 10171-2016 standard to test the surface resistance at room temperature (25°C), and used a universal alkaline electrolytic hydrogen production cell to test the cell voltage of the actual electrolytic hydrogen production process (the smaller the cell voltage, the lower the power loss). The cell cross-sectional area of ​​the cell used was 0.0314m 2 .

[0091] Table 1 Comparison of performance of diaphragms of embodiments and comparative examples

[0092]

[0093]

[0094] It can be seen from the examples that in actual use, the diaphragm we prepared, without adding additional heating equipment, relies on the natural heating during the electrolysis process (the temperature will be maintained at about 45°C), the chamber voltage is comparable to that of the traditional PPS fabric diaphragm at 90°C and the surface resistance is significantly reduced; it can be seen that the diaphragm can be used in room temperature electrolysis process.

[0095] The hydrogen production membrane provided by the present invention has a thickness of 300-500 μm and a surface resistance of ≤0.1 Ω / cm 2 , at an electrolysis temperature of 90°C and a current density of 5000A / m 2 Under the test conditions, the cell voltage is ≤1.05V.

[0096] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A water electrolysis hydrogen production diaphragm with a burr structure, characterized in that: The diaphragm is composed of a supporting wire mesh and a composite porous layer with a burr structure, and the supporting wire mesh is located in the middle of the composite porous layer; The composite porous layer has vertical through holes with large apertures and mesh composite small holes, and the vertical through holes and mesh composite small holes are all burr-shaped holes; The composite porous layer contains an alkali-resistant polymer, a hydrophilic modified inorganic substance and a hydrophilic modified auxiliary agent; The preparation method of the diaphragm is as follows: firstly, a casting liquid is prepared according to a preset formula, wherein the casting liquid contains a pore-forming agent, a pore-forming auxiliary agent, an organic solvent, an alkali-resistant polymer, a hydrophilic modification auxiliary agent and a hydrophilic modification inorganic substance; then, a support screen is prepared, and the casting liquid is scraped onto the surface of the support screen to obtain a semi-finished diaphragm; finally, the diaphragm is cured by a coagulation bath and post-processed to obtain a finished diaphragm; The pore-forming agent is compounded by polyvinyl pyrrolidone of different molecular weights; The compounding relationship is: the molecular weight of the high molecular weight PVP is 80w-150w, the molecular weight of the low molecular weight PVP is 28000-54000, the mass ratio of the high molecular weight PVP to the low molecular weight PVP is 5-6:5-6; the total mass of the pore-forming agent is 50-75% of the mass of the alkali-resistant polymer; The pore-forming auxiliary agent is gum arabic, and the mass of the pore-forming auxiliary agent is 10-15% of the mass of the alkali-resistant polymer.

2. The diaphragm according to claim 1, characterized in that The material of the support wire mesh is polyphenylene sulfide or polyetheretherketone; the support wire mesh is woven from monofilaments, the weaving density is 20-100 meshes, and the diameter of the monofilaments is 30-150 microns.

3. The diaphragm according to claim 1, characterized in that The burr structure has a hydrophilic surface and a capillary effect.

4. The diaphragm according to claim 1, characterized in that The thickness of the diaphragm is 300-500 μm; the standard surface resistance at room temperature is ≤0.1Ω / cm 2 , at an electrolysis temperature of 90°C and a current density of 5000A / m 2 Under the test conditions, the cell voltage is ≤1.05V.

5. A method for preparing the diaphragm according to any one of claims 1 to 4, characterized in that: First, a casting liquid is prepared according to a preset formula, wherein the casting liquid contains a pore-forming agent, a pore-forming auxiliary agent, an organic solvent, an alkali-resistant polymer, a hydrophilic modification auxiliary agent and a hydrophilic modified inorganic substance; then a supporting wire mesh is prepared, and the casting liquid is scraped onto the surface of the supporting wire mesh to obtain a semi-finished diaphragm; finally, the diaphragm is cured in a coagulation bath and post-treated to obtain a finished diaphragm.

6. A preparation method according to claim 5, characterized in that: The specific steps include: S1: dissolving the pore-forming agent and the pore-forming auxiliary agent in an organic solvent, adding an alkali-resistant polymer after dissolution and ensuring complete dissolution, to obtain a mixed solution I; S2: adding a hydrophilic modification auxiliary agent to the mixed solution I and mixing evenly, slowly adding the hydrophilic modification inorganic powder under stirring conditions, stirring until no obvious particles are present, and then cooling to obtain a casting solution; S3: prepare a supporting screen, set the height of the scraper to a preset thickness, use the casting liquid obtained in S2 to scrape the film, and let it stand for a period of time after the scraping is completed to obtain a semi-finished diaphragm; S4: Immerse the semi-finished diaphragm in a coagulation bath for solidification, and after the diaphragm is completely solidified, wash it with deionized water to obtain a finished diaphragm.

7. The preparation method according to claim 5, characterized in that: The pore-forming agent is compounded by polyvinyl pyrrolidone of different molecular weights; The compounding relationship is: the molecular weight of the high molecular weight PVP is 80w-150w, the molecular weight of the low molecular weight PVP is 28000-54000, the mass ratio of the high molecular weight PVP to the low molecular weight PVP is 5-6:5-6; the total mass of the pore-forming agent is 50-75% of the mass of the alkali-resistant polymer.

8. The preparation method according to claim 5, characterized in that: The pore-forming auxiliary agent is gum arabic, and the mass of the pore-forming auxiliary agent is 10-15% of the mass of the alkali-resistant polymer.

9. The preparation method according to claim 5, characterized in that: The hydrophilic modified inorganic substance is one or more of nano zirconium oxide, nano titanium oxide and nano cerium oxide; the added amount is 80-120% of the mass of the alkali-resistant polymer.

10. The preparation method according to claim 5, characterized in that: The hydrophilic modification auxiliary agent is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, fatty acid methyl ester ethoxylate sodium sulfonate, and alkylphenol polyoxyethylene ether; the mass of the hydrophilic modification auxiliary agent is 15-28% of the mass of the alkali-resistant polymer.

Citation Information

Patent Citations

  • Ceramic capillary ion dialysis diaphragm for power lithium battery, and preparation method of ceramic capillary ion dialysis diaphragm

    CN108281598A

  • Gel electrolyte diaphragm as well as preparation method and application thereof

    CN114204217A